Alterações estruturais e funcionais do ventrículo esquerdo associadas à leucemia aguda antes da quimioterapia: um estudo com speckle tracking por ecocardiografia bidimensional - Leal, Bruna Morhy Borges [UNIFESP] (2018)
Background: Patients with acute leukemia (AL) have a higher rate of congestive heart failure than patients with other cancers. AL may predispose to cardiac dysfunction before chemotherapy because of high cytokine release or direct leukemic myocardial infiltration. The aims of this study were to evaluate whether AL is associated with abnormalities of myocardial structure and function before chemotherapy and to identify possible risk factors associated with these myocardial changes. Methods: Using an echocardiographic database, 76 patients with AL and 76 patients without cancer matched for age, gender, hypertension, and the presence of diabetes were retrospectively selected. Subsequently, to assess the effect of a nonhematologic malignancy, 28 women in each group were matched with women with breast cancer. Left ventricular (LV) mass, volumes, ejection fraction, and global longitudinal strain (GLS) were measured before chemotherapy. Results: The patients were predominantly male (63%), with a median age of 51 years, and had low prevalence of cardiovascular risk factors. Despite similar LV ejection fractions, patients with AL had higher LV mass and volumes and lower GLS (-19.3 ± 2.7% vs -20.9 ± 1.9%, P<0.001) than patients without cancer. Similarly, GLS was lower in women with AL compared with women with breast cancer or without cancer. Among patients with AL, high body mass index, low LV ejection fraction, and a small number of circulating lymphocytes were all independently associated with low GLS. Conclusions: Patients with AL had higher LV volumes and lower GLS than patients without cancer and lower GLS than patients with breast cancer, suggesting that AL by itself may be associated with these cardiac alterations.